Evaluating failure mechanisms of excavation-induced large-scale landslides in Xinjing open-pit coal mine through integrated UAV imagery and 3D simulation - Li, Jinduo; Yang, Tianhong; Deng, Wenxue; Du, Shigui; Zhang, Zirui; Ma, Haitao; Wang, He; Guo, Jiateng; Liu, Lijie (Landslides, 2025)
On February 22, 2023, at 13:12, a major landslide occurred at the Xinjing open-pit coal mine in Inner Mongolia, resulting in 53 fatalities, 6 injuries, and a direct economic loss of approximately 200 million RMB. This incident highlights the high risk of instability posed to gently dipping anti-dip rock layers by excavation activities under complex geological conditions. Herein, a three-dimensional slope analysis method integrating high-resolution terrain modeling, automated structural plane identification, and InSAR monitoring is proposed. Initially, high-resolution aerial imagery was used to generate a surface model with millimeter-level precision. An automated structural plane recognition system was then employed to identify 1327 structural joints and major faults, pinpointing potential hazard zones and confirming that wedge failure is the primary instability mode of this slope. Subsequently, InSAR data were used to capture surface deformation acceleration leading up to the landslide event. A three-dimensional (3D) numerical simulation was conducted to assess slope deformation characteristics and stability variations at different excavation depths. At excavation depths exceeding 90 m, slope deformation considerably intensifies, and fault activation causes a rapid decline in the safety factor, greatly increasing the risk of instability. To ensure long-term slope stability, a mitigation strategy combining slope cutting and wide platform installation is proposed. This study demonstrates the benefits of high-precision 3D analysis in slope stability assessment, providing critical technical support for slope design and protection under complex geological conditions.